Diagnostic accuracy of serological and imaging tests used in surveillance for hepatocellular carcinoma in adults with cirrhosis: a systematic review protocol [version 2; peer review: 2 approved] - Stephen Ryder; Matthew Cramp; Nicky Welton; Ken Stein; John Bell; Felicity Oppe; Gabriel Rogers; Libby Sadler; Penny Whiting; Hayley Jones; Kelsey Watt; Morwenna Rogers (NIHR Open Research, 2024)
Background Liver cirrhosis is the largest risk factor for developing hepatocellular carcinoma (HCC), and surveillance is therefore recommended among this population. Current guidance recommends surveillance with ultrasound, with or without alpha-fetoprotein (AFP). This review is part of a larger project looking at benefits, harms and costs of surveillance for HCC in people with cirrhosis. It aims to synthesise the evidence on the diagnostic accuracy of imaging or biomarker tests, alone or in combination, to identify HCC in adults with liver cirrhosis in a surveillance programme. Methods We will identify studies through a 2021 Cochrane review with similar eligibility criteria, and a database search of MEDLINE, Embase and the Cochrane Database of Systematic Reviews. We will include diagnostic test accuracy studies with adult cirrhosis patients of any aetiology. Studies must assess at least one of the following index tests: ultrasound (US), magnetic resonance imaging (MRI), computerised tomography (CT), alpha-fetoprotein (AFP), des-gamma-carboxyprothrombin (DCP), lens culinaris agglutinin-reactive fraction of AFP (AFP-L3), a genomic biomarker, or a diagnostic prediction model incorporating at least one of the above-mentioned tests. We will assess studies for risk of bias using QUADAS-2 and QUADAS-C. We will combine data using bivariate random effects meta-analyses. For tests evaluated across varying diagnostic thresholds, we will produce pooled estimates of sensitivity and specificity across the full range of numerical thresholds, where possible. Where sufficient studies compare two or more index tests, we will perform additional analyses to compare the accuracy of different tests. Where feasible, we will stratify all meta-analyses by tumour size and patient characteristics, including cirrhosis aetiology and liver disease severity. Discussion This review will synthesise evidence across the full range of possible surveillance tests, using advanced statistical methods to summarise accuracy across all thresholds and to compare the accuracy of different tests. PROSPERO registration CRD42022357163